Peramalan Tingkat Inflasi Kota Medan Menggunakan Metode Arima Box Jenkins - Sinaga, Dina; Susiana, Susiana (ULIL ALBAB : Jurnal Ilmiah Multidisiplin, 2024)
The city of Medan is one of the indicators for calculating inflation in the province of North Sumatra. so the Medan City government must maintain the increase in inflation to remain stable as one of the conditions so that economic growth remains sustainable and is beneficial for improving people’s welfare. By recording inflation data in the previous period and predicting inflation data for the next period, the behavior of a region’s inflation data can be observed. The aim of this research is to forecast inflation for the city of Medan using the ARIMA Box Jenkins method. In forecasting Medan city inflation using the ARIMA method, three transformation processes are carried out so that the Medan city inflation data is stationary with respect to variance, and without a differencing process. Three ARIMA forecasting models were obtained, namely ARIMA (1,0,0), ARIMA (0,0,1), and ARIMA (1,0,1). The best model of the three models that have been obtained is ARIMA (0,0,1). forecasting inflation for the city of Medan for the next two years, namely 2025 with an inflation value of 2196.